Interdisciplinary Perspectives on Virtual Place-Based Learning - Lansiquot, Reneta D.; MacDonald, Sean P. (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
XV, 166 p. 18 illus., 16 illus. in color.